Exercise and Dairy Protein have Distinct Effects on Indices of Liver and Systemic Lipid Metabolism. Issue 1 (15th November 2019) - Townsend, Logan K.; Gandhi, Shivam; Shamshoum, Hesham; Trottier, Sarah K.; Mutch, David M.; Reimer, Raylene A.; Shearer, Jane; LeBlanc, Paul J.; Wright, David C.
Abstract : Objective: This study aimed to explore the individual and combined effects of skim milk powder (SMP) and exercise on indices of systemic and liver lipid metabolism in male obese rats. Methods: Rats were fed a high‐fat (~ 40% kcal from fat), high‐sugar diet for 8 weeks. At 12 weeks of age, rats were assigned to one of four weight‐matched, isocaloric, high‐fat, high‐sugar groups for 6 weeks: (1) casein‐sedentary, (2) casein‐exercise, (3) SMP‐sedentary, and (4) SMP‐exercise. Nonfat SMP or casein was the sole protein source in the dairy and control casein diets, respectively. Exercise training occurred 5 d/wk for 60 minutes on a motorized treadmill. Whole‐body metabolism was assessed by a Comprehensive Lab Animal Monitoring System. Lipidomics, Western blot, and polymerase chain reaction were used to assess markers of hepatic lipid metabolism. Results: Exercise, but not SMP, altered the fatty acid composition of liver triglycerides, reduced indices of lipogenesis, and increased expression of genes linked to oxidative metabolism, in conjunction with increases in whole‐body fat oxidation. SMP and exercise reduced plasma triglycerides in an additive manner. Conclusions: These findings provide evidence that SMP and exercise exert distinct effects on whole‐body and hepatic carbohydrate and lipid metabolism and that they could work in a synergistic manner to reduce serum triglyceride concentrations.